Novelty, Knowledge Spillovers and Innovation: Evidence from Nobel Laureates - John C. Ham; Bruce A. Weinberg (Global Labor Organization (GLO), 2017)
Using a new identification strategy and unique, rich data on Nobel laureates, we show that being in new or multiple locations, as measures of exposure to novel combinations of ideas, and the number of other local important innovators, all increase the probability that eventual Nobel laureates begin their Nobel prize winning work. Strikingly, and consistent with our identifying assumptions, we find that none of these measures increase the probability of doing Nobel prize winning work. Our results strongly suggest that spillovers affect the generation of ideas, and help us understand the weak spillover effects previously estimated in the economics literature.
Keywords: 330; Knowledge spillovers; Innovation; Nobel Prize; Duration models